How have interventions targeting pregnant women from refugee, migrant and culturally and linguistically diverse backgrounds living in high-income countries been developed or tailored to meet community needs? A systematic scoping review of stillbirth-related literature - Sweekriti Sharma; Gayathri Jegadeesh; Camille Raynes-Greenow; Adrienne Gordon; Gayani Gunawardhana; Danielle Marie Muscat (BMC Pregnancy and Childbirth)
Abstract Background People from migrant, refugee and culturally and linguistically diverse backgrounds experience significant disparities in pregnancy outcomes compared to the general population, including a higher risk of stillbirth. This study aimed to identify stillbirth-related programs or interventions for pregnant women from culturally and linguistically diverse backgrounds and explore how these interventions have been developed and/or tailored for culturally and linguistically diverse women. Methods We searched MEDLINE, CINAHL, Embase, and Scopus for articles published from inception to 12 Jan 2023. We included studies that report on the development and/or evaluation of a program or intervention to reduce the risk of stillbirth which has been specifically developed or tailored for pregnant women from culturally and linguistically diverse backgrounds living in high-income countries. Two independent reviewers conducted screening of the articles, data extraction, and quality appraisal. We first summarized the descriptive information of eligible studies using text and tables and then thematically grouped interventions based on approaches to meet community needs and synthesized data qualitatively. Results We identified 1999 studies from the database search. After removing duplicates and screening for eligibility, 9 studies met our inclusion criteria and were included in the review. Studies were conducted in Australia, the UK, US and Denmark between 1986 and 2021, with multi-ethnic populations (n = 6) or specific cultural and language groups (n = 3) (e.g. Pakistani and Indian women; African American and Hispanic population groups). Approaches to tailoring included the use of interpreters and translated materials, linking women to existing community resources and networks and community outreach delivered to women outside of hospital settings. Training of staff in cultural competence and multi-component, multiagency interventions addressing the wider social determinants of health and system-based approaches to facilitate access to language services were also identified. Conclusion While there are currently few targeted interventions for pregnant women from migrant, refugee and culturally and linguistically diverse backgrounds, approaches to cultural tailoring identified in this review can be used as a starting point for effectiveness testing and wider application. Ongoing work is needed to continue to address significant disparities in pregnancy outcomes for minoritised community groups. Protocol registration The protocol for this review was registered in PROSPERO (CRD42021289321).